Testing The Determinants Of Corporate Reputation And Their Impact On Market Valuation - Tamara Limbunan; Fransiskus Eduardus Daromes (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study examines model of the determinants of corporate reputation, namely managerial ability and corporate social performance and their impact on market valuation. Theoretical model is built based on Resource-based theory and signaling theory. Population of this study are all companies listed on the Indonesia Stock Exchange in 2017 – 2020. The results of this study indicate that there is an influence between managerial ability and corporate social performance on corporate reputation. This study also finds that corporate reputation has an effect on market valuation, however, both managerial ability and corporate social performance have no effect on market valuation. Subsequent testing shows that corporate reputation mediates the relationship between managerial ability and corporate social performance on market valuation.